The challenges experienced by probation officer in the facilitation of diversion programmes: Social work perspective - Tshivhase, Jerry (Technium Social Sciences Journal, 2025)
This manuscript explores the challenges experienced by Probation officers (P.O) in the facilitation of diversion programmes. The study employed exploratory, contextual, descriptive, and phenomenological research designs, following the stages outlined by Creswell (2014) for data analysis. The data collected using a semi-structured interview guide was analyzed using Tesch’s framework for thematic analysis. Ethical requirements such as informed consent, confidentiality, anonymity, voluntary participation, and the avoidance of harm were adhered to throughout the study. The study revealed numerous challenges that POs are confronted with when rendering diversion programme on a daily basis; namely low level of education, behaviour of the children during the programme, lack of resources, limited number of POs, accessibility of diversion programmes, training of POs, supervision of POs and as a result they are affecting the effectiveness of the programmes. The study recommended that the Department of Social development should avail themselves to mitigate the challenges in the facilitation of diversion programmes. It must provide resources for the probation officers in order for them to render effective services, the number of POs rendering diversion programmes must be increased, the programmes must be accessible to the children, training of POs and supervision must be improved.